Understanding the Corrosion Resistance of Meso- and Micro-Porous Carbons for Application in PEM Fuel Cells. Issue 6 (28th March 2018) - Forouzandeh, Farisa; Li, Xiaoan; Banham, Dustin W.; Feng, Fangxia; Ye, Siyu; Birss, Viola
Abstract : The stability of carbon support materials is critical to the lifetime of proton exchange membrane (PEM) fuel cells. Here, we have used a rigorous potential stepping and i/t analysis regime to compare the corrosion resistance of the commonly used microporous carbon black powder, Vulcan carbon (VC), with that of a family of hard-templated mesoporous colloid-imprinted carbon (CICs, with monodisperse pore sizes ranging from 10–50 nm), also using heat-treatment (at 1500°C under N2 for 2 h) to help understand and differentiate their stability. It was found that VC is more corrosion-resistant than the CICs, as VC was already heat-treated at > 1400°C during its preparation, while the CICs experienced a maximum of 900°C during their in-house synthesis. Consistent with this, the CICs have a higher surface density of graphene sheet edges, which are prone to oxidation, and yet these sites are also better at nucleating and stabilizing Pt nanoparticles. Importantly, the smaller the CIC pore size, the better its corrosion resistance, while heat-treatment makes both VC and the CICs more corrosion resistant, giving a 40–60% increase in durability. This is attributed to enhanced hydrophobicity and crystallinity of the carbons and a decrease in the density of defects.